PENDIDIKAN MORAL DALAM CERITA ANAK œSAMOSIR DAN œKELINCI YANG SERAKAH BAGI ANAK SEKOLAH DASAR - Harahap, Muharrina; Chairunnisa, Hera; Khairani, Ita; Anggreini, Heny (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2022)
The purpose of this study was to determine moral education in the children's stories "Samosir" and "The Greedy Rabbit". By knowing the moral education of children's stories, it is clear that these children's stories can build the character and social character of elementary school children; educating the emotional, spiritual, and intelligence of elementary school children. This goal is motivated by the problem that moral education must be presented from an early age to children through children's stories, especially elementary school children. However, not infrequently the children's stories that are presented actually contain values that are far from building morals. Based on this problem, a research was carried out using Clifford Geertz's symbolic interpretive study with a qualitative descriptive method. The results of this study are the children's stories "Samosir" and "The Greedy Rabbit" contain moral education. However, these children's stories can also damage the morale and psyche of children if they are interpreted 'as they are'. Children can be constructed that if they make a mistake, they will receive a very big punishment. This can put pressure on the psyche of children so they are afraid to do something or do something wrong.